E-Commerce sebagai Media Promosi dalam Peningkatan Daya Saing Produk UMKM MOSS 1 di Kabupaten Jember - Lenny Luthfiyah; Rizky Yanuarti; Indah Ibanah; Laily Mutmainnah; Restiani Sih Harsanti (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
This community service was carried out by the women's group Mother School Sumbersari (MOSS) 1 Sumbersari Jember. The MOSS 1 group's main activities are religious . Mothers are taught to recite the holy Qur'an with teaching staff from the local Religius Office Affairs (KUA). Apart from studying religion, MOSS 1 also has entrepreneurial activities that produce food and beverage products. However, MOSS 1 has problems with product promotion and sales. Product sales are carried out in a simple way, starting from direct sales, safekeeping in stores, and simple promotions via WhatsApp (WA) status. The purpose of implementing community service is at the stage of having an impact on understanding competitive marketing strategies through e-commerce. The method used is to use interactive training methods. Activities carried out by discussing the sales process that has been running. Then education regarding the use of e-commerce using the lecture method and training on creating e-commerce accounts. The results obtained from the implementation of this community service are the understanding of the participants regarding the differences in marketing through WA and e-commerce. Further dedication will be carried out with digital marketing managerial for e-commerce management.